Generalized scenarios of transition to chaos in ideal dynamic systems - Олексій Горчаков; Олександр Швець (Sistemnì Doslìdženâ ta Informacìjnì Tehnologìï)
The implementation of a new scenario of transition to chaos in the classical Lorenz system has been discovered. Signs of the presence of an implementation of the generalized intermittency scenario for dynamic systems are described. Phase-parametric characteristics, Lyapunov characteristic exponents, distributions of invariant measures, and Poincaré sections are constructed and analyzed in detail, which confirm the implementation of the generalized intermittency scenario in an ideal Lorenz system.